Acute pneumonia: infection or inflammation in the lung? - I., Klepikov (Journal of Respiratory Diseases, 2019)
This commentary examines pneumonia as infection and inflammatory syndrome, parsing diagnostic criteria and implications for antimicrobial stewardship.